Influence of Dietary Salt Intake on T2D Treatment - Li, Li; Mi, Yuwei; Xu, Miao; Ruan, Liemin; Sun, Jie; Song, Qifa (Frontiers in Endocrinology, 2022)
Backgrounds: To what extent patients undergoing long-term T2D treatment are affected by dietary salt intake has not been completely investigated. Objectives: We aimed to investigate the influence of dietary salt intakes on T2D treatment, including glucose-lowering effect and indices related to T2D progression. Methods: The study recruited 1090 patients with T2D at Ningbo City First Hospital from January 1, 2018, to December 30, 2021. We compared their one-year follow-up outcomes in terms of fasting blood glucose (FBG), glycated hemoglobin (HbA1c), blood pressure, obesity, and prevalence of retinopathy and neuropathy among groups with different dietary salt intakes. Results: The 1090 patients consisted of 287(26.3%) decreasing-, 190(17.4%) increasing-, 175(16.0%) steadily low-, 243(22.3%) steadily medium-, and 195(17.9%) steadily high-dietary salt intake patients. Compared to increasing-, steadily medium-, and steadily high-dietary salt intake patients, decreasing and steadily low salt intake led to lower baseline FBG, HbA1c, systolic blood pressure (SBP), BMI, and visceral fat area (VFA) (all p<0.05), to a larger decrease in FBG, HbA1c, SBP, BMI, and VFA after one-year treatment (all p<0.05), as well as to a slightly lower prevalence of retinopathy and a significantly lower prevalence of neuropathy. The steadily low salt patients had lower urine albumin/creatinine ratio (UAR) both at baseline and after treatment. Notably, the fasting insulin in the steadily low salt group was higher than the remaining group after treatment (p<0.01). Conclusions: The present study concludes that lowered dietary salt intake benefits T2D treatment in multiple aspects, including main treatment targets such as FBG and HbA1c, and indices reflecting potential complications of T2D, including BMI, VFA, SBP, UAR, retinopathy, and neuropathy.